Finite Element analysis of stress state in the cement of total hip prosthesis with elastomeric stress barrier - Allaoua Fadela (Gruppo Italiano Frattura, 2021)
In the total hip prosthesis, according to different positions of the patient, there are a variety of loads acting on femoral head which generate stress concentration in the cement called polymethylmethacrylat (PMMA) and consequently in the interfaces stem/cement/bone. This load transfer can provoke loosening of the implant from the femoral bone. This paper focused on optimal stress distribution in the total hip prosthesis and devoted to the development of a redesigned prosthesis type in order to minimize stress concentration in the cement. This study investigated the effect of elastomeric stress barrier incorporated between the stem and femoral head using 3D-finite element analysis. This proposed implant provoked lower load transfer in the cement due to the elastomeric effect as stress absorber.  However, the proposed model provided an acceptable solution for load transfer reduction to the cement. This investigation permitted to increase the service life of the total hip prosthesis avoiding the loosening.